The impact of Marketing Agility on Marketing Performance: The Role of Competition as a Moderating Variable in the context of SMEs - Wisanggeni Bagus Anggoro; Najmudin Najmudin; Sudarto Sudarto (International Journal of Business and Quality Research, 2024)
This article discuss the importance of marketing agility to increase the marketing performance in the high level of competitiveness. Marketing agility known for usefullness to face the uncertian condition of the market. But lot of studies only implemented in the big company, only few research was done in the context of small business. This research collecting data from small business in the central java. Using the structured equation modeling the data was analyzed to get the result. The result shows that high competitiveness level will increase the impact of marketing agility on the marketing performance. This study has a limitation because the data only collected in vew resident in central java and only using cross sectional data, future research may try using time series data and expand the research area.